The influence of adverse childhood experiences on attention deficit hyperactivity disorder. - Ramesh, Kalpina; Shujaat, Tabia; Kumar, Dinesh (Journal of the Pakistan Medical Association, 2025)
Madam, Adverse Childhood Experiences (ACEs) are characterized by distressing experiences before they turn 18. ACEs encompass parental loss, maltreatment—such as abuse or neglect—and parental challenges like violence, incarceration, mental illness, or substance use.(1) These traumatic experiences can disrupt brain development, increasing the likelihood of neurological and behavioural disorders including attention-deficit/hyperactivity disorder (ADHD).(2) Research suggests a strong correlation between ACEs and incidence of developing ADHD, with certain adversities, such as poverty, domestic violence, community violence, and parental mental illness, playing a significant role in Pakistani children.(3) This aligns with the findings from the National Survey of Children’s Health, demonstrating that exposure to specific ACEs, including poverty, parental divorce, familial mental illness, neighbourhood violence, and parental incarceration, substantially increases the susceptibility to ADHD, particularly in its moderate to severe forms.(1) The overlapping symptoms between Post Traumatic Symptom Disorder (PTSD) and ADHD complicates the clinical evaluations in Pakistan, where children exposed to ACEs exhibit behavioural and emotional dysregulation, resembling ADHD.(3) For instance, hypervigilance due to trauma may be mistaken for ADHD-related distractibility and impulsivity may result from a stress response rather than a neurodevelopmental disorder.(2) With up to 58% women reporting at least one ACE and many children exposed to violence and neglect,(4,5) clinicians risk misdiagnosing trauma-related behaviours as ADHD without proper screening, resulting in inappropriate treatment plans.(2,3) Addressing the association between ACEs and ADHD raises concern, especially in Pakistan where declining socioeconomic conditions, may suggest underdiagnosis of ADHD in underdeveloped areas. Government initiatives to alleviate economic stability, expand mental health services, provide public education and parental support, are essential to mitigate ADHD risks. Reducing mental health stigma through awareness campaigns and parental counselling can aid early diagnosis, reduce isolation and foster understanding. Enhancing psychiatrist availability by tackling affordability, accessibility, and long wait times further encourages intervention. Culturally sensitive premarital counselling programs could promote responsible family planning, improving socioeconomic prospects. Additionally, a trauma-informed approach integrating ADHD management such as cognitive-behavioural therapy (CBT) and mindfulness-based strategies is crucial in handling their compounded effects.